Perceived Effectiveness of Tutorial Program in Improving Mathematics Academic Performance - Mariño, Ednalane Mae; Saluria, Raymark Anthony (Journal of Interdisciplinary Perspectives, 2024)
Tutorial programs are one of the many techniques that educational institutions have been experimenting with to improve students' mathematical skills due to realizing the importance of mathematics in the curriculum. This study assessed the influence and effectiveness of tutoring programs on junior high school pupils’ academic performance in Mathematics. The results show that children from various age groups, grade levels, and socioeconomic backgrounds frequently receive individual tutoring, especially in subjects like math and Filipino. Both parents and kids perceive the tutorial program as a highly successful educational intervention that improves learning and gives students more self-assurance when facing mathematical difficulties. Teachers also acknowledge tutorial programs as a beneficial teaching resource that improves students' academic performance. The study demonstrates no substantial correlation between students' academic ability in mathematics and the level of effectiveness of the tutorial program. Although tutoring can provide tailored assistance and promote comprehension, other elements might be more critical in determining academic achievement. Furthermore, a tutorial program is an excellent complement to the educational support structure, offering advantages for various educational backgrounds and demographics.